An exploratory analysis of the relationship between purchase category strategies and supply base structure. Issue 3 (September 2015) - Ateş, Melek Akın; Wynstra, Finn; van Raaij, Erik M.
Abstract This article explores how purchasing strategy at the purchase category level is related to the structure of the supply base for that purchase category. We contrast cost strategies with innovation strategies, and define supply base structure as being comprised of size (number of suppliers), heterogeneity (differentiation of suppliers), interaction (competition/collaboration), time/stability (contract duration) and transparency (supplier information sharing). Examining 13 purchase categories by means of the multiple case study method, we find that supply base structures that are associated with higher purchasing performance are not only explained by differences in purchase category strategy, but also by the purchase category's impact and supply risk. We develop seven detailed propositions for future research on this complex interplay.